PEMBUATAN ANODA BERDIMENSI STABIL GRAFITILa203âZr02 DAN APLIKASINYA UNTUK EKSTRAKSI ELEKTROLITIK ALUMINIUM = PREPARATION OF GRAPHITE/La203âZr02 DIMENSIONALLY STABLE ANODE AND ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The dimensionally stable anode graphite/La203âZr02 has been made and used for electrolitycal extraction process of aluminium from AlC13 solution in the liquid mixture of NaCl/LiC1 at Â± 700Â°C. The anode was prepared by coating the mixture of La203âZr02 on the graphite by thermal decomposition technique of LaCI3 and ZrOCl2.8H20. It was concluded that the mol fraction of La coated in the graphite was smaller than that in the boater solution, while on the contrary for Zr. The electrolysis using graphite coated by La203 and Zr02 in the mol ratio of 3 : 7 at 3.00 Volt of voltage and 0.016 Ampere of current for an hour produced 5.372 mg of aluminium. The rendement of faraday was 85.63%. Key Words: Electrolitycal extraction, thermal decomposition technique, rendement of faraday.